The role of symbolism in moral education: a study of the ruwat murwakala ritual - Budhi, Lardianto; Subiyantoro, Slamet; Wahida, Adam; Sularso, Sularso (Institut Seni Indonesia Surakarta, 2023)
This essay is the outcome of a study on the Ruwat Murwakala, a traditional cleaning event for humans of sukerta that also serves as a backdrop for Javanese culture and religion. Although it is a religious activity, the ceremony serves as a moral education for society by conveying several symbols of worth. The mantra, one of the key components of the murwakala ceremony, is the subject of this investigation. This study used semiotic analysis of Ferdinand de Saussure's model and qualitative research methods. According to de Saussure, this symbol or sign can be understood through the idea of the relationship between the signifier and the signified. Reading the four fundamental mantras is the most important part of the ritual in Ruwat Murwakala's tale since it serves as a means of overcoming Bathara Kala. The primary methods for gathering data for this study were interviews and literature reviews. Direct observation and audio-visual recordings of the observation item were also used to obtain data. After then, the triangulation method was used to examine all of the data. The findings indicated that the four primary mantras chanted by the dalang during the Ruwat Murwakala procedure have symbolic meanings that include moral instruction about the tenets of human behaviour. This study examines educational resources from local traditional literature sources to demonstrate the significance of the idea of culture-based moral education. The findings of this study aid in the creation of community-wide moral education resources using an artistic and cultural perspective.